Modifikasi Roll Air Seal Mill Pulverizer MPS 89 PLTU Suralaya - Arief Suardi Nc; Retno Aita Diantari; Eri Sukoco (Sekolah Tinggi Teknik - PLN, 2015)
Suralaya Power Plant using Mill Pulverizer MPS-89 as a tool for coal-fired nourishing that will be transmitted to the boiler fuel in. Coal miners To sublimate Mill Pulverizer MPS-89 using Home Wheel Tire and Grinding Ring segment. Grinding Ring segment digerakan by motor, while Home Wheel Tire follow Ring Segments and relies on cushioning material. The damage safeguards Home Wheel Tire because kemasukkan dust from coal, will cause stopping operations of mill pulverizer, thus affecting